Applications of calcium isotopes in marine carbonates in the Recent and Phanerozoic - Blättler, C (2012)
The applications of calcium-isotope measurements in marine carbonates are explored in several different contexts within this thesis. As a record of global ion fluxes, seawater calcium-isotope ratios can be used as tracers for large weathering imbalances, which develop as a feedback system in response to intervals of climate change. This approach provides valuable constraints on the complex climatic and oceanographic phenomena known as the Oceanic Anoxic Events. Over much longer timescales, the calcium-isotope ratio of seawater is influenced by steady-state processes that reflect the evolution of seawater chemistry. To understand these influences, the modern calcium-isotope budget is assessed quantitatively using a compilation of marine carbonate samples, revealing several distinctive components of the carbonate burial sink that can affect the steady-state balance of the calcium cycle. Changes in the major ion composition of seawater and in the organisms that contribute to sedimentary carbonate burial are shown to contribute significantly to the geological record of seawater calcium-isotope ratios. The importance of skeletal carbonate in the calcium cycle leads to another application of calcium isotopes towards understanding biomineralization. This large and complex topic is approached with calcium-isotope data from two unique growth experiments that constrain some of the mechanisms by which biogenic aragonite acquires its geochemical signatures. This range of topics presents a diverse, but by no means exclusive, sample of the topics that are accessible for investigation through calcium-isotope analysis. The potential of this isotopic tool is demonstrated by the breadth of environments and timescales represented in this work.